2017
DOI: 10.1080/21645515.2017.1285475
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a trivalent inactivated influenza vaccine produced in Shenzhen, China

Abstract: A split-virion trivalent inactivated influenza vaccine produced according to the Chinese pharmacopeia (Shz-IIV3) has been commercially available in China since 2014. Here, we describe the results of a phase IV open-label trial to describe the immunogenicity and safety of the 2014–2015 Northern Hemisphere formulation of Shz-IIV3 in individuals ≥ 6 months of age. Subjects 6–35 months of age received 2 half-doses of Shz-IIV3 (0.25 ml) 28 d apart, and subjects ≥ 3 y of age received a single full dose (0.5 ml). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
5
10
0
2
Order By: Relevance
“…Solicited injection site reactions were reported by similar proportions of subjects in the Shz-IIV3 and comparator IIV3 groups (31.4% vs. 33.0%), as were solicited systemic reactions (12.8% vs. 12.1%) ( Table 3). Consistent with other studies of IIV3, 10,16 the most frequently reported solicited reactions in each group were malaise, myalgia, and pain and erythema at the injection site (Supplemental Table 1). For both groups, most solicited reactions were grade 1 (mild) in intensity and most resolved within 3 days.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Solicited injection site reactions were reported by similar proportions of subjects in the Shz-IIV3 and comparator IIV3 groups (31.4% vs. 33.0%), as were solicited systemic reactions (12.8% vs. 12.1%) ( Table 3). Consistent with other studies of IIV3, 10,16 the most frequently reported solicited reactions in each group were malaise, myalgia, and pain and erythema at the injection site (Supplemental Table 1). For both groups, most solicited reactions were grade 1 (mild) in intensity and most resolved within 3 days.…”
supporting
confidence: 87%
“…These results are in line with an earlier study that showed the 2014-2015 Northern Hemisphere formulation of Shz-IIV3 was highly immunogenic in Chinese individuals ≥6 months of age. 10 Post-vaccination HAI GMTs and seroconversion rates for Shz-IIV3 were statistically non-inferior to those for the comparator IIV3, for all three vaccine strains ( Table 2). Because non-inferiority was shown for all six analyses, Shz-IIV3 was considered to demonstrate overall non-inferiority versus the comparator vaccine.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Ao longo dos anos, vários estudos clínicos pré e pós comercialização, com vacinas de influenza trivalente sazonal (fragmentada e inativada), semelhantes à vacina produzida pelo IB, foram realizados (33)(34)(35)(36)(37)(38)(39)(40) .…”
Section: Estudos Clínicos De Vacina Influenza Trivalente Sazonal (Fraunclassified
“…A reação adversa local observada com maior frequência, tanto em adultos quanto nos idosos, nos três estudos, foi dor no local da aplicação da vacina, e a sistêmica cefaleia. Tais reações adversas também têm sido descritas na literatura como as principais reações adversas associadas a imunização com vacina influenza sazonal trivalente e inativada (33,(35)(36)(37) . Os poucos episódios de febre observados também são reconhecidos como potenciais reações adversas associadas a este tipo de vacina e não são considerados graves ou associados às complicações (52) .…”
Section: Tamanho Amostralunclassified